SANTO PAULUS Sang Misionaris Agung - Hariprabowo, Yacobus (UNIKA Santo Thomas, 2009)
The Apostle Paul has always had a special fascination for missionaries. Through the years several monographs on Paul’ significance for the Christian mission have been written by missionaries and missiologists. The missionary dimension of Paul’ theology has not always been recognized. For many years he was primarily regarded as the creator of dogmatic system. With the rise of the history-of-religions school he was viewed pre-eminently as a mystic. Later still the emphasis shifted to the ecclesiastical Paul. Only very gradually did biblical scholars discover that Paul was first and foremost to be understood, also in his letters, as a great missionary.